Effect of Carbohydrate Content in a Pre-event Meal on Endurance Performance-Determining Factors: A Randomized Controlled Crossover-Trial - Aandahl, Mats Holst; Noordhof, Dionne A.; Tjønna, Arnt Erik; Sandbakk, Øyvind (Frontiers in Sports and Active Living, 2021)
Purpose: To investigate the effect of the relative CHO content in a pre-event meal on time to exhaustion (TTE), peak oxygen uptake (V̇O2peak), the 2nd lactate threshold (LT2), and work economy (WE) and to compare responses between well-trained and recreationally trained individuals. Methods: Well-trained (n=11) and recreationally trained (n=10) men performed three trials in a randomized cross-over design, in which they performed exercise tests 1) after a high-CHO pre-event meal (3 g ∙ kg-1), 2) a low-CHO pre-event meal (0.5 g ∙ kg-1), or 3) in a fasted-state. The test protocol consisted of five submaximal 5-min constant-velocity bouts of increasing intensity and a graded exercise test (GXT) to measure TTE. A repeated measure ANOVA with a between-subjects factor (well-trained vs recreational) was performed. Results: A main effect of pre-event meal was found (p = 0.001), with TTE being 8.0% longer following the high-CHO meal compared to the fasted state (p = 0.009) and 7.2% longer compared to the low-CHO meal (p = 0.010). No significant effect of pre-event meal on V̇O2peak, LT, or WE (p ≥ 0.087) was found and no significant interaction effect between pre-event CHO intake and training status was found for TTE or any of the performance-determining variables (p ≥ 0.342). Conclusions: A high-CHO content in the pre-event meal led to a longer TTE compared to a meal with a low-CHO content or exercising in a fasted state, both in well-trained and recreationally trained participants. The underlying physiological cause for the increased TTE is unclear, as no effect of pre-event meal on the main physiological performance-determining variables was found. Thus, pre-event CHO intake should be standardized when the goal is to assess endurance performance but seems to be of less importance when assessing the main performance-determining variables.